Energy efficiency initiatives in a campus building - Abidin, Nur Izieadiana (UTM LOW CARBON RESEARCH CENTRE, 2016)
Higher Learning Institution (HLI)is a place for ademicians, students and its administration staff in a campus. HLI is among the favoured targeted locations to embrace for sustainability and energy conservation solutions due to the campus operations and activities that have significant energy consumption depending on the size of the campus including its buildings and infrastructures. Basically, there are several alternatives for which HLI is able to offer huge opportunities in retrofitting initiatives to concern on energy efficiency. This paper presents a study leads to the identification of possible retrofit initiatives and the criteria affecting the retrofitting of M50 building in Faculty of Civil Engineering towards zero energy. A questionnaire survey was distributed to occupants of M50 building in order to identify the preferred energy efficiency technologies to be implemented. The result was analyzed with Relative Importance Index (RII) and it shows that solarphotovoltaic, green roof and variable air volume were among the most preferable technologies. The relevant criteria for each energy efficiency initiatives being prioritized and ranked based on Factor Analysis (FA. The purpose of using the selected approach and ranking is to investigate the significance of each criteria. The performing result assists as a step for energy efficiency initiatives in a campus building, thus minimizing the energy impact to environment from its operations and activities. The study outcome is also indirectly fulfilling an example case for sustainable teaching, learning and research process.